1969
DOI: 10.1083/jcb.43.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Osmium Zinc Iodide Reactive Sites in the Epidermal Langerhans Cell

Abstract: Fixation of epidermis with a mixture of osmium tetroxide and zinc iodide (Os0 4 -ZnI 2) for 24 hr renders the central periodic lamella of the Langerhans cell granule (LCG), the Golgi region, and the nuclear envelope of epidermal Langerhans cells preferentially visible . The use of this technique on Langerhans cells in normal epidermis and in epidermis of patients with histiocytosis (Letterer-Siwe disease) allows a broader visualization of the LCG's than was heretofore possible with routine glutaraldehyde-osmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

1971
1971
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…The authors (Niebauer et al 1969, Elias et a1. 1972 suggest that the Znh-OsO4 mixture could form com plexes with the phospholipids and with the insaturated lipids.…”
Section: Remarks About the Osmium Impregnationmentioning
confidence: 99%
“…The authors (Niebauer et al 1969, Elias et a1. 1972 suggest that the Znh-OsO4 mixture could form com plexes with the phospholipids and with the insaturated lipids.…”
Section: Remarks About the Osmium Impregnationmentioning
confidence: 99%
“…Stelzner (1971) (21) suggested that the ER-staining was consistent in oligodendroglia during myelination and endothelial cells during capillary growth, both of which were actively synthesizing lipids. The other work (13) indicated that the osmium deposit almost disappeared from the tissues after the lipid extraction. From a spectrophotometrical study, Riemersma (1968) (20) showed that Os04 could react with lipids, especially the unsaturated fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…In some cell types, this technique is of use in preferential staining for not only the Golgi apparatus but also other cytoplasmic organelles (5,7,9,10,12,13,18,20).…”
mentioning
confidence: 99%
“…The lymph nodes of the animals were then quickly removed. Specimens were immersed in the zinc iodide-osmium tetroxide (ZIO) solution by Niebauer et al (1969) and kept in the dark for 2 hours in this solution from temperature for fixation/staining.…”
Section: Methodsmentioning
confidence: 99%